2011
DOI: 10.1348/026151010x533229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early child-care on cognition, language, and task-related behaviours at 18 months: An English study

Abstract: Data were drawn from a prospective longitudinal study of 1,201 infants. As found in previous studies, sociodemographic characteristics and maternal caregiving (especially "opportunities for stimulation") were significant predictors of all child outcomes. There were also effects of quantity of individual and group care, and quality of non-maternal care. Controlling for demographics and maternal caregiving, more hours of group care (nurseries) were related to higher cognitive scores, while more hours of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
71
0
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 58 publications
18
71
0
15
Order By: Relevance
“…Similarly, Sylva et al14 reported that mothers with higher levels of education choose school environments that are richer in stimuli for child development, as they understand the day care center as an important environment for development, and not just a child-care place during their working time. Regarding the socioeconomic factor, there was no correlation with the child's performance, although it is a risk factor well described in the literature 8…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sylva et al14 reported that mothers with higher levels of education choose school environments that are richer in stimuli for child development, as they understand the day care center as an important environment for development, and not just a child-care place during their working time. Regarding the socioeconomic factor, there was no correlation with the child's performance, although it is a risk factor well described in the literature 8…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal analysis of amount of time spent in non-maternal childcare showed inconsistent findings; some suggested significant association with child cognitive outcomes [13], some others did not [2,5,6,9]. Significant associations were found when types of childcare were examined separately.…”
Section: Patterns Of Childcare and Cognitive Developmentmentioning
confidence: 99%
“…Significant associations were found when types of childcare were examined separately. Attending centre-based childcare predicted higher cognitive ability as early as 18 months [5] and at age three [3]. Some other studies, however, found no significant relation between early centre-based childcare and later cognitive ability [2,14].…”
Section: Patterns Of Childcare and Cognitive Developmentmentioning
confidence: 99%
See 2 more Smart Citations